Educators as Connectors: Bridging the Equivalence Gap Between Online and Face-To-Face Learning in Tertiary Education - Michelle Roberts; Steven Pace; Amy Johnson (Student Success)
The rapid growth in online education has amplified significant challenges in providing equivalent peer connection experiences across study modes.  This article examines which educator practices, as identified by students, support equivalent peer connections in online and face-to-face study modes. Using constructivist grounded theory methodology, we conducted in-depth interviews with 15 undergraduate students at an Australian university who had experienced both delivery modes. Our analysis establishes four essential elements for enabling equivalent peer connection experiences: informal conversations, initial connection opportunities, peer visibility, and educator presence. From these findings, we developed a framework of equivalent educator practices that bridge the modal equivalence gap. This student-informed framework provides practical guidance for educators, ensuring all students have access to the academic and social benefits peer connection provides.